Stability of cruciform specimens for fracture tests under compression. (15th February 2022) - Giannella, V.; Amato, D.; Perrella, M.
Highlights: Cruciform specimens under tensile and compressive loading were simulated by FEM. Modal-based geometric imperfections were considered to avoid bifurcation points. A central notch with two cracks were added to calculate K values. Usage of one specimen for fracture tests under large compressive loads was validated. Multiple aspects to design fracture biaxial tests under compression were highlighted. Abstract: Cruciform specimens have been developed in the last decades in order to evaluate the fatigue and fracture material behaviour under biaxial stress fields. These evaluations have been generally conducted under positive load ratios, so as to prevent the potential buckling of these generally thin specimens. This paper reports a numerical investigation on the stability of two cruciform specimens in order to provide useful information for the design of biaxial fracture tests under both tension and compression. Two cruciform geometries were selected among those widely accepted in literature and slightly modified so as to apply equal boundary conditions. FEM simulations were performed under tensile and compressive loading conditions by considering geometric imperfections based on the superposition of the buckling modes. Results were cross-compared in terms of stress fields, load–displacement curves, stress intensity factors and critical loads along crack propagation. Guidelines of general validity were derived.